Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) as Platform for the Targeted Multimodal Tumor Therapy - Janko, Christina; Ratschker, Teresa; Nguyen, Khanh; Zschiesche, Lisa; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Frontiers in Oncology, 2019)
Standard cancer treatments involve surgery, radiotherapy, chemotherapy and immunotherapy. In clinical practice, the respective drugs are applied orally or intravenously leading to the systemic circulation in the whole organism. For chemotherapeutics or immune modulatory agents, severe side effects such as immune depression or autoimmunity can occur. At the same time the intratumoral drug doses are often too low for effective cancer therapy. Since monotherapies often cannot cure cancer, due to their synergistic effects multimodal therapy concepts are applied to enhance treatment efficacy. The targeted delivery of drugs to the tumor by employment of functionalized nanoparticles might be a promising solution to overcome these challenges. For multimodal therapy concepts and individualized patient care nanoparticle platforms can be functionalized with compounds from various therapeutic classes (such as radio sensitizers, phototoxic drugs, chemotherapeutics, immune modulators). Superparamagnetic iron oxide nanoparticles (SPIONs) as drug transporters can add further functionalities, such as guidance by external magnetic fields (Magnetic Drug Targeting), heating by external magnetic fields (Magnetic Hyperthermia), and imaging-controlled therapy (Magnetic Resonance Imaging).